2018
DOI: 10.1590/0004-282x20180077
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in individuals with spinocerebellar ataxia type 10: a preliminary study

Abstract: In this sample, the greatest impairment of QoL in individuals with SCA10 was observed in "physical functioning" and "physical role".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…Depression were consistently reported in several studies on SCA, and this could correlate significantly with quality of life [22,30]. As mentioned previously that mobility is the main concern, depression levels were also seen lower in those subjects with better mobility [6,25]. Even when other causes of depression may revolve around memory and learning ability disorders, most SCA subjects would have learning difficulty in limb control, which becomes a vicious cycle and a hazard for them to perform well in mobile activities of daily living [5].…”
Section: Environmental and Personal Factorsmentioning
confidence: 65%
See 3 more Smart Citations
“…Depression were consistently reported in several studies on SCA, and this could correlate significantly with quality of life [22,30]. As mentioned previously that mobility is the main concern, depression levels were also seen lower in those subjects with better mobility [6,25]. Even when other causes of depression may revolve around memory and learning ability disorders, most SCA subjects would have learning difficulty in limb control, which becomes a vicious cycle and a hazard for them to perform well in mobile activities of daily living [5].…”
Section: Environmental and Personal Factorsmentioning
confidence: 65%
“…A number of studies have also reported that difficulty in verbal memory, learning, and fluency are commonly seen [16,24]. These cognitive disorders would sum into a restriction in several community participation, but motor abilities still remained to inflict the most significant effect to quality of life in SCA [25]. Reports have mentioned the involvement of visuospatial and executive functioning abilities being reduced in SCA3, as it may correlate with reduced cerebellar perfusion [16].…”
Section: Activity and Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…People with ataxia have been shown to have significant static and dynamic imbalance, which can directly affect their self-care, transfers and locomotion functions (Aizawa et al, 2013). It can lead to a significant decrease in daily life activities and social participation and can increase the dependency of people (Santos et al, 2018). Basic BAT strengthens the individual's "body ego" and increases confidence in one's body (A. L. .…”
Section: S P E C I a L S E C T I O N : P H Y S I O T H E R A P Y F O mentioning
confidence: 99%